Direct selling: From door to door to e-commerce - Alturas, B. (2003)
Direct selling is exhibiting substantial growth in sales revenues and number of salespeople involved. Also the acceptation of consumers is growing. During the last decade direct selling organizations (DSOs) are using the Internet more and more, either to communicate with the salespersons, either to promote the products and the business to the consumers. This research contributes to a better understanding DSOs’ use of the Internet, based on the interview of 11 managers of DSOs operating in Portugal. Results show that DSOs use the Internet as a support to their main business. We then discuss aspects of importance for further extensions.